Performance of sesenduk wood [Endospermum diadenum (Miq.) airy shaw], semantan bamboo (Gigantochloa scortechinii gamble) and laminated compressed products treated with low viscosity melamine urea formaldehyde resin - Mohd Ali, Rabi'atol Adawiah (2019)
Low density wood is one of potential raw material to be used in reducing dependency on commercial timber species. However, these woods are relatively poor in properties and require special treatment to enhance their properties before they can be further utilized into high value-added products. There have been many attempts to enhance the properties of low density wood through bulking treatment with low molecular weight phenol formaldehyde (LmwPF) and the results showed that the physic-mechanical properties and durability of the treated materials were improved significantly. However, due to the oligomer state of the resin, high free formaldehyde is emitted. Therefore, a study was undertaken to formulate low viscosity melamine urea formaldehyde (MUF) that can be served as a bulking agent as well as to maintain its adhesion properties. The MUF resin was synthesized at different amount of melamine (20 to 30%), urea (10 to 25%) and formaldehyde (50 to 60%) and the solution was diluted to gain concentrations of 20% and 30%. It was found that MUF formulation (F4) which consist of 30% melamine, 50% formaldehyde and 20% urea had a viscosity of 9 cP, 118 min pre-curing time, 24 min curing time and 32% solid content which is believed to have excellent bulking and adhesion properties. Thus, this formulation was used to treat sesenduk (Endospermum diadenum) wood and bamboo (Gigantochloa scrtechinii). Air-dry samples were treated separately with the synthesized MUF solutions using empty cell process. The impregnated materials were pre-cured at 70ºC and followed by curing at 140ºC. The other set of treated samples, they were undergone hot compressing at 140ºC immediately after pre-curing and the resultant product is known as compressed material. Commercial MUF was also used as treating solution for comparison purposes. The results show that the impregnant had successfully penetrated and bulked the cell wall of the material as indicated by the positive values of density (44 to 55%), polymer loading (27 to 55%) and bulking coefficient (3.8 to 7.8%). Lower PDI value for the synthesized resin (1.12) as compared to commercial MUF (1.19) was due to smaller particles and dispersion of the formulated resin which is essential for the impregnant to penetrate the wood cell wall. Excellent penetration of the MUF resin was also proven by micrograph from scanning electron microscope (SEM) which show lumen cells and voids were occupied with the MUF resin. It was also found that the treatment had successfully imparted dimensional stability where the water absorption was reduced to 32% and anti-swelling coefficient was improved for 48%. The bulked resin managed to increase mechanical strength of the wood strips as the MOR increased up to 17% and MOE increased up to 59% when compared to the untreated wood. The MUFcompressed strips treated with higher melamine content resin likes 30% F4 yield the lowest formaldehyde emission (FE) of 0.94 ppm and was categorized in E2 class. The formaldehyde emission was very low due to formation of methylene bridge (melamine formaldehyde) which were spotted in few peaks in spectroscopic analysis of FTIR-UATR. In the second phase of the study, several products were produced, viz. laminated wood, laminated bamboo, laminated wood/bamboo hybrid and laminated untreated wood. In terms of dimensional stability, WA and ASE of formulated MUF-compressed products were excellent than treatment using commercial MUF. For the mechanical properties, MOR and MOE significantly increased parallel to increasing of density. The commercial MUF-compressed products had greater MOR and MOE than formulated MUF-compressed products. The high solid content of the commercial resin cause greater bulking of the resin into wood cells that make the wood stronger and more stiff. Generally, it was found that formulated MUF-compressed sesenduk produced the highest shear strength compared to another treatments. However, the hardness and tensile strength of the compressed products treated with commercial MUF was greater due to high bonding strength between wood and resin. Durability of the laminated compressed products against white rot fungus was determined where the treatments has included the products into durable category with weight loss values less than 4%. The durability of the treated products was improved for 66 to 83% as compared to the untreated wood which explain that the formulated MUF resin has bulked the lumen cell resulting in prevention of water bonding and the resin itself became toxic to the fungus.